When (distant) relatives stay too long: implications for cancer medicine. Issue 1 (December 2016) - Chowell, Diego; Boddy, Amy; Mallo, Diego; Tollis, Marc; Maley, Carlo
Abstract Whole-genome analyses of human medulloblastomas show that the dominant clone at relapse is present as a rare subclone at primary diagnosis.